2015
DOI: 10.1016/j.jval.2015.09.1573
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Adverse Drug Events on Health Resources Utilizaton in Older Adult Singaporeans

Abstract: A517number of expedited approval programs. The objective of this study was to evaluate these programs by examining whether drugs included in them have provided larger health gains than drugs excluded from them. Methods: We considered the FDA's priority review, accelerated approval, and fast-track programs. We estimated health gains in terms of quality-adjusted life-years (QALYs) for drugs approved for the first time between 1999 and 2011, relative to treatments available at the time of their approval. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…At a rate of US$570,400 per 1000 patients, the direct annual ADR burden in Singapore is estimated to be US$168 million, almost 5% of the annual operating healthcare expenditure [31]. The median cost of US$2951 was also much higher than the SGD1015 (~US$734) reported previously in elderly patients from the same institution, likely because of different ADR detection methods (ICD codes vs. manual review) [3]. In this study, bleeding and/or elevated INR due ADR adverse drug reaction, INR international normalized ratio a Suspected drugs were classified according to the Anatomical Therapeutic Chemical (ATC) classification system [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a rate of US$570,400 per 1000 patients, the direct annual ADR burden in Singapore is estimated to be US$168 million, almost 5% of the annual operating healthcare expenditure [31]. The median cost of US$2951 was also much higher than the SGD1015 (~US$734) reported previously in elderly patients from the same institution, likely because of different ADR detection methods (ICD codes vs. manual review) [3]. In this study, bleeding and/or elevated INR due ADR adverse drug reaction, INR international normalized ratio a Suspected drugs were classified according to the Anatomical Therapeutic Chemical (ATC) classification system [42].…”
Section: Discussionmentioning
confidence: 99%
“…Data on ADR-associated costs in Singapore are scant. In a recent study, ADRs were identified using International Classification of Diseases (ICD) codes in patients ≥ 65 years old, and the median hospitalization cost per patient with ADRs was estimated to be $1015 (2013 SGD, approximately US $811) [3]. On the higher end, the median cost of hospitalization for chemotherapy-induced febrile neutropenia in cancer patients was $3964 (2012 SGD, approximately US $3171) [4].…”
Section: Introductionmentioning
confidence: 99%